Structural Characterization, and Antioxidative and Anti-inflammatory Activities of Phylloxanthobilins in Tropaeolum majus, a Plant with Relevance in Phytomedicine - Frei, Patricia; Nadegger, Christian; Vollmar, Angelika M.; Müller, Thomas; Moser, Simone (Planta Medica, 2024)
Tropaeolum majus (garden nasturtium) is a plant with relevance in phytomedicine, appreciated not only for its pharmaceutical activities, but also for its beautiful leaves and flowers. Here, we investigated the phytochemical composition of senescent nasturtium leaves. Indeed, we identified yellow chlorophyll catabolites, also termed phylloxanthobilins, which we show to contribute to the bright yellow color of the leaves in the autumn season. Moreover, we isolated and characterized the phylloxanthobilins from T. majus, and report the identification of a pyro-phylloxanthobilin, so far only accessible by chemical synthesis. We show that the phylloxanthobilins contribute to bioactivities of T. majus by displaying strong anti-oxidative effects in vitro and in cellulo, and anti-inflammatory effects as assessed by COX-1 and COX-2 enzyme inhibition, similar to other bioactive ingredients of T. majus, isoquercitrin, and chlorogenic acid. Hence, phylloxanthobilins could play a role in the efficacy of T. majus in the treatment of urinary tract infections, an established indication of T. majus. With the results shown in this study, we aid in the completion of the phytochemical profile of T. majus by identifying additional bioactive natural products as relevant components of this medicinal plant.
Keywords: Tropaeolum majus; Tropaeolaceae; antioxidant; anti-inflammatory properties; phylloxanthobilins; pyro-phyllobilin; phytochemicals